Renal health after long-term exposure to tenofovir disoproxil fumarate (TDF) in HIV/HBV positive adults in Ghana. Issue 6 (June 2018) - Villa, G.; Phillips, R.O.; Smith, C.; Stockdale, A.J.; Beloukas, A.; Appiah, L.T.; Chadwick, D.; Ruggiero, A.; Sarfo, F.S.; Post, F.; Geretti, AM
Highlights: Long-term treatment with TDF was safe in HIV/HBV-positive patients on stable care. Tubular proteinuria was significantly higher in women and hypertensive patients. Concomitant ritonavir-boosted lopinavir accelerated eGFR decline in subjects on TDF. HBVDNA load, transaminases and liver stiffness did not predict renal abnormalities. Screening for co-morbidities is needed in sub-Saharan Africa to optimise HIV care. Summary: Objectives: The study assessed markers of renal health in HIV/HBV co-infected patients receiving TDF-containing antiretroviral therapy in Ghana. Methods: Urinary protein-to-creatinine ratio (uPCR) and albumin-to-protein ratio (uAPR) were measured cross-sectionally after a median of four years of TDF. At this time, alongside extensive laboratory testing, patients underwent evaluation of liver stiffness and blood pressure. The estimated glomerular filtration rate (eGFR) was measured longitudinally before and during TDF therapy. Results: Among 101 participants (66% women, median age 44 years, median CD4 count 572 cells/mm 3 ) 21% and 17% had detectable HIV-1 RNA and HBV DNA, respectively. Overall 35% showed hypertension, 6% diabetes, 7% liver stiffness indicative of cirrhosis, and 18% urinary excretion of Schistosoma antigen. Tubular proteinuria occurred in 16% of patients and was independently predicted by female gender and hypertension. The eGFR declined by median 1.8 ml/min/year during TDF exposure (IQR −4.4, −0.0); more pronounced declines (≥ 5 ml/min/year) occurred in 22% of patients and were associated with receiving ritonavir-boosted lopinavir rather than efavirenz. HBV DNA, HBeAg, transaminases, and liver stiffness were not predictive of renal function abnormalities. Conclusions: The findings mandate improved diagnosis and management of hypertension and suggest targeted laboratory monitoring of patients receiving TDF alongside a booster in sub-Saharan Africa.